Lagging regions and development strategies: The case of Peru - Thurlow, James; Morley, Samuel; Nin-Pratt, Alejandro (International Food Policy Research Institute, 2009)
Despite the economic transformation of Peru’s coastal economy, the country’s inland region remains poor and underdeveloped. We herein examine the economic linkages between the two regions using a multi-regional computable general equilibrium model based on a regionalized social accounting matrix. The model results show that coastal growth undermines the inland economy by increasing import competition and internal migration. Peru, therefore, cannot rely solely on rapid national growth to generate broad-based poverty reduction. When we simulate policies aimed at curbing divergence, we find that reducing interregional transaction costs stimulates national economic growth, but widens divergence by shifting inland production towards agriculture and concentrating investment in coastal manufacturing. In contrast, conditional cash transfers reduce regional and rural-urban inequality, but do not stimulate national growth. Finally, investing in inland productivity (through extension services and improved rural roads) reduces regional divergence, but the resulting market constraints worsen rural-urban inequality. These findings suggest that isolated interventions may worsen inequality, and that complementarities exist between supply-side investments and policies aimed at stimulating demand and improving access to national markets.